Tacrolimus‐induced hypomagnesemia and hypercalciuria requires FKBP12 suggesting a role for calcineurin - Brittany D. K. Gratreak (Physiological Reports, 2020)
Abstract Calcineurin inhibitors (CNIs) are immunosuppressive drugs used to prevent graft rejection after organ transplant. Common side effects include renal magnesium wasting and hypomagnesemia, which may contribute to new‐onset diabetes mellitus, and hypercalciuria, which may contribute to post‐transplant osteoporosis. Previous work suggested that CNIs reduce the abundance of key divalent cation transport proteins, expressed along the distal convoluted tubule, causing renal magnesium and calcium wasting. It has not been clear, however, whether these effects are specific for the distal convoluted tubule, and whether these represent off‐target toxic drug effects, or result from inhibition of calcineurin. The CNI tacrolimus can inhibit calcineurin only when it binds with the immunophilin, FKBP12; we previously generated mice in which FKBP12 could be deleted along the nephron, to test whether calcineurin inhibition is involved, these mice are normal at baseline. Here, we confirmed that tacrolimus‐treated control mice developed hypomagnesemia and urinary calcium wasting, with decreased protein and mRNA abundance of key magnesium and calcium transport proteins (NCX‐1 and Calbindin‐D28k). However, qPCR also showed decreased mRNA expression of NCX‐1 and Calbindin‐D28k, and TRPM6. In contrast, KS‐FKBP12−/− mice treated with tacrolimus were completely protected from these effects. These results indicate that tacrolimus affects calcium and magnesium transport along the distal convoluted tubule and strongly suggests that inhibition of the phosphatase, calcineurin, is directly involved.